Analysis of Meridian Flow in Gas Turbines: Design and Performances - Belkacem, Bendjaima (Techniques and Innovation in Engineering Research Vol. 6, 2022)
Performance optimization is an ongoing challenge in any industry. Increases in turbomachinery performance are frequently required in the field of electrical energy production. One method for achieving this goal is to design new machines from existing ones. This work incorporates this step by utilizing the absorption cooler and scale factor concepts. The theoretical calculation started after analyzing the reception essays findings of the initial machine authorized validation, and the outcomes are utilized to determine the scale factors expression for the new machines design. Using this idea, together with a combustion air cooling system, a performance analysis of the suggested machine is conducted (the absorption cooler). A numerical calculation of the scale factor and performances was also performed.